Fiscal Incentive Policy Implementation for Compliant Taxpayers in Optimizing Local Own-Source Revenue in North Minahasa Regency, Indonesia - Christian A. Katuuk; Joseph Philip Kambey; Steven V. Tarore (International Journal of Information Technology and Education, 2026)
This article examines the implementation of a fiscal incentive policy for compliant taxpayers as a strategy for optimizing local own-source revenue in North Minahasa Regency, Indonesia. The study is positioned within public administration, local fiscal governance, taxpayer compliance, and policy implementation scholarship. Using a qualitative descriptive design, data were collected through interviews, documentation, and secondary data review involving regional leaders, revenue agency officials, technical tax officers, and stakeholders related to local tax administration. The findings show that the fiscal incentive policy has been developed through a systematic sequence of policy formulation, administrative and legal review, taxpayer database preparation, determination of compliance criteria, socialization, and technical execution. The policy has a positive strategic role because it shifts local tax administration from a predominantly punitive approach toward a more persuasive, service-oriented, and motivational approach. However, implementation has not yet reached optimal effectiveness. The main constraints include inadequate taxpayer data validity, uneven socialization, limited human resource capacity, insufficient operational infrastructure, weak standard operating procedures, and incomplete technical guidelines. The article argues that fiscal incentives can support voluntary compliance and PAD optimization only when they are supported by accurate data, institutional coordination, consistent communication, clear procedures, and monitoring systems. The study contributes to public administration literature by demonstrating that local revenue innovation depends not only on regulatory authority but also on administrative readiness, public trust, service quality, and behavioral compliance mechanisms.